2021
DOI: 10.1177/08862605211045096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Maltreatment Among Canadian National Team Athletes

Abstract: This study assessed the prevalence of maltreatment experienced by Canadian National Team athletes. In total, 995 athletes participated in this study, including current athletes and athletes who had retired in the past 10 years. An anonymous online survey was administered, consisting of questions about experiences of psychological, physical, and sexual harm, and neglect, as well as questions about identity characteristics, when the harm was experienced, and who perpetrated the harm. Neglect and psychological ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
4
47
0
2
Order By: Relevance
“…Interpersonal violence (IV) against young athletes has recently been defined as violence between individuals including violence by an adult in a position of authority, such as the coach, violence between athletes, and violence by spectators ( Parent and Fortier, 2018 ). While sexual violence against young athletes is one of the more concerning threats in the media (see the scandals of Dr. Larry Nassar, who sexually abused hundreds of young American gymnasts, and Sarah Abitbol, French skater who was sexually abused by her coach during her early career), other forms of IV have also been identified, such as psychological violence (e.g., Stirling and Kerr, 2013 ), physical violence (e.g., Stafford et al, 2013 ), and neglect ( Willson et al, 2021 ). Psychological violence includes restriction of movement and patterns of belittling, denigrating, scapegoating, threatening, scaring, discriminating, ridiculing, and other non-physical forms of hostile treatment or rejection ( World Health Organization, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal violence (IV) against young athletes has recently been defined as violence between individuals including violence by an adult in a position of authority, such as the coach, violence between athletes, and violence by spectators ( Parent and Fortier, 2018 ). While sexual violence against young athletes is one of the more concerning threats in the media (see the scandals of Dr. Larry Nassar, who sexually abused hundreds of young American gymnasts, and Sarah Abitbol, French skater who was sexually abused by her coach during her early career), other forms of IV have also been identified, such as psychological violence (e.g., Stirling and Kerr, 2013 ), physical violence (e.g., Stafford et al, 2013 ), and neglect ( Willson et al, 2021 ). Psychological violence includes restriction of movement and patterns of belittling, denigrating, scapegoating, threatening, scaring, discriminating, ridiculing, and other non-physical forms of hostile treatment or rejection ( World Health Organization, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of Safe Sport initiatives stemmed from high-profile cases of athlete abuses as well as various prevalence studies indicating the frequency with which athletes from various levels of sport experience harm ( Alexander et al, 2011 ; Vertommen et al, 2016 ; Parent and Vaillancourt-Morel, 2020 ; Willson et al, 2021 ). In addition to highlighting the prevalence of harmful experiences, these studies suggested that athletes in equity-deserving 2 groups experience more harm in sport.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a prevalence study conducted by Vertommen et al (2016) , females reported significantly more experiences of sexual violence in sport compared to males. In Canada, Willson et al (2021) explored the prevalence of maltreatment experienced by current and retired Olympic and Paralympic athletes; both current and retired female athletes reported significantly more experiences of neglect, as well as psychological, physical and sexual harm, than their male counterparts. Additionally, findings from the 2020 Athlete Culture and Climate Survey launched by the United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations